Evaluation of Nutritional Status of Rural Bengalee Primary School Boys (6-9 Years) in Comparison to Indian Children - Dutta, Subrata; Dhara, Prakash Chandra (International Journal of Child Health and Nutrition, 2013)
A cross sectional study was undertaken to determine nutritional status and growth pattern of 410 rural primary school boys (6-9 years of age) belong from lower socioeconomic status according Kuppuswamy's socioeconomic scale (2012) in West Midnapore District of West Bengal. The daily nutritional intake of the children was measured by weighing raw and cooked foods and also by 24 hrs recall method. The body mass indexes (BMI), body composition, protein/calory adequacy status, protein-energy ratio of the primary school boys were measured to assess the nutritional status. The food and nutrient intake of the subjects were compared with their respective Indian values (NNMB, 2002). The diet of rural school boys was found to be imbalanced with plenty intake of milk and lower in intake of cereals, pulses but higher in intake of vegetables than that of their Indian counterpart. It was observed that the diets are predominantly more deficient in calories than protein. Most of the boys had normal body weight and only a little number of boys was overweight or underweight and the protein energy ratio is lower than ICMR recommended value except the age group of 7 years and the maximum percentage (about 20%) of underweight boys is found in the age group of 9 years. It was further observed that there was a significant correlation between body composition and BMI (p<0.001).